Ejecución presupuestaria de gastos del Gobierno Autónomo Descentralizado Parroquial Rural de Ricaurte en el periodo 2022. - Anzoategui Triana, Norkis Arelis (2024)
This case study was carried out in the Ricaurte parish GAD, in the Urdaneta canton, Los Ríos Province; The Decentralized Autonomous Government (GAD) of the Rural Parish of Ricaurte, an institution belonging to the public sector, is politically, administratively and financially independent, it is committed to providing services to the entire community in order to improve the quality of life of the people who They make up the parish. To this end, the study titled “Budget Execution of expenses of the Rural Parochial Decentralized Autonomous Government of Ricaurte in the period 2022” is based on the need to analyze the company based on its budget execution for the year 2022. Understand how the entity manages its resources, since inconsistencies have a negative impact and prevent all originally planned activities from being carried out. To do this, both qualitative and quantitative methods are used, which use quantifiable variables and experiences to analyze from a human perspective. The results that were obtained and their respective debate gave way to the analysis and interpretation of the findings followed by the conclusions and recommendations of this scientific investigation, where the main points of the researcher are directly related to the objectives. The financial planning of the Ricaurte rural parish GAD seeks to understand and provide control, improve decision making; and the degree to which the entity's goals and objectives are achieved. Planning is a resource of great importance since it adapts to different areas and aspects of business and personal life. The purpose of this article is to identify how financial planning has become a sustainable factor in public organizations.